Issues on Design of Piled Raft Foundation (JOURNAL OF ADVANCES IN CHEMISTRY, 2018)
A piled raft foundation consists of a thick concrete slab reinforced with steel which covers the entire contact area of the structure, in which the raft is supported by a group of piles or a number of individual piles. Bending moment on raft, differential and average settlement, pile and raft geometries are the influencing parameters of the piled raft foundation system. In this paper, a detailed review has been carried out on the issues on the raft foundation design. Also, the existing design procedure was explained.